1991
DOI: 10.1161/01.hyp.17.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Salt blocks the renal benefits of ramipril in diabetic hypertensive rats.

Abstract: To establish if the benefit of angiotensin converting enzyme inhibitor therapy in retarding progressive diabetic renal injury is due to a specific intrarenal effect or the systemic hypotensive effect, we studied the effect of long-term ramipril treatment on blood pressure, glomerular filtration rate, and urinary protein excretion in streptozotocin-diabetic spontaneously hypertensive rats. The hypotensive effect of ramipril was prevented by a high salt diet, which did not alter the degree of renal angiotensin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
4
10
0
Order By: Relevance
“…4,5 Salt retention often found in diabetic patients not only attenuates the antihypertensive efficacy of ACE inhibition but may also interfere with the cardiac and renoprotective actions of ACE inhibitors. 39 This study has suggested an additional blood pressure-lowering effect of dual NEP/ACE inhibition in SHR with streptozotocin-induced diabetes and may therefore have an important bearing on treatment of hypertension in diabetic patients. However, one must be cautious in extrapolating the present findings in rodents to humans.…”
Section: Discussionmentioning
confidence: 77%
“…4,5 Salt retention often found in diabetic patients not only attenuates the antihypertensive efficacy of ACE inhibition but may also interfere with the cardiac and renoprotective actions of ACE inhibitors. 39 This study has suggested an additional blood pressure-lowering effect of dual NEP/ACE inhibition in SHR with streptozotocin-induced diabetes and may therefore have an important bearing on treatment of hypertension in diabetic patients. However, one must be cautious in extrapolating the present findings in rodents to humans.…”
Section: Discussionmentioning
confidence: 77%
“…1 Clinical studies suggest that the combination of CCB and CEI may be superior in decreasing proteinuria compared with the respective monotherapy. 2 Despite the evidence for a beneficial effect of this combination on blood pressure 37 and proteinuria 2 in hypertensive patients, there are no data as to the effect of CCB plus randomly divided into seven groups: (1) untreated hypertensive rats (HC, n=18), (2) untreated normotensive rats (NC, n=10), (3) rats treated with enalapril (100 mg/L drinking water, n=9; Merck Sharp & Dohme, Munich, Germany), (4) rats treated with nitrendipine (1 mg/g diet, n=12; Bayer, Leverkusen, Germany), (5) rats treated with enalapril and nitrendipine (ENP+NIT) (same dosage as in monotherapy, n=12), (6) rats treated with enalapril and hydrochlorothiazide (ENP+HCTZ) (enalapril same dosage as in monotherapy; hydrochlorothiazide, 50 mg/L drinking water, n=12; Sigma, Deisenhofen, Germany), and (7) 7 days withdrawal of nitrendipine after 6 weeks therapy with nitrendipine (PNIT, n=9).…”
Section: ^3:114-122)mentioning
confidence: 99%
“…1-3, 6 The efficacy of treatment, however, is heterogeneous and dependent on inborn 7 and environmental [8][9][10][11][12] factors. Data in experimental diabetes, 13,14 adriamycin nephrosis, 15 uninephrectomized rats, or in Munich Wistar rats with spontaneously reduced nephron numbers 16 uniformly show that expansion of the sodium pool, with glomerular hyperfiltration and activation of the renal RAS induced by enhanced sodium intake, all contribute to blunt the BP and proteinuria lowering effect of RAS inhibitors. 17 Consistently, observational studies in humans showed that increased dietary sodium intake increases proteinuria and accelerates renal disease progression.…”
mentioning
confidence: 99%